Light based cellular interactions: hypotheses and perspectives - Laager, Frederic (Frontiers in Physics, 2015)
This work investigates the theoretical possibility of interactions between cells via light. We first take a brief look at the previous research done in the past to have a better understanding of the field and the origins of the concept of cellular interactions. Then we identify the different elements essential for interactions between two parties. We then compare the required elements with the known and studied elements and characteristics which are well defined in biology, chemistry and physics. This way we are able to set up four postulates required for cell interactions: I. A signal is present and subject to secondary modulation by the emitter cells. II. There is a plastic information medium that reacts directly to the metabolic state of the emitter and therefore carries information about the emitter. III. An optical signal can be perceived by cells on a molecular level by a multitude of different receptors. IV. The information can in theory be processed by cells and metabolic changes in reaction to the signals can be observed. We demonstrate that all required elements have been observed. Most of them have important and well-known roles in cells. Therefore, we suggest that our hypothetical model is a good explanation for light based cellular interactions.